4y-3+y+37=7x+40-4y

Simple and best practice solution for 4y-3+y+37=7x+40-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-3+y+37=7x+40-4y equation:


Simplifying
4y + -3 + y + 37 = 7x + 40 + -4y

Reorder the terms:
-3 + 37 + 4y + y = 7x + 40 + -4y

Combine like terms: -3 + 37 = 34
34 + 4y + y = 7x + 40 + -4y

Combine like terms: 4y + y = 5y
34 + 5y = 7x + 40 + -4y

Reorder the terms:
34 + 5y = 40 + 7x + -4y

Solving
34 + 5y = 40 + 7x + -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
34 + 5y + 4y = 40 + 7x + -4y + 4y

Combine like terms: 5y + 4y = 9y
34 + 9y = 40 + 7x + -4y + 4y

Combine like terms: -4y + 4y = 0
34 + 9y = 40 + 7x + 0
34 + 9y = 40 + 7x

Add '-34' to each side of the equation.
34 + -34 + 9y = 40 + -34 + 7x

Combine like terms: 34 + -34 = 0
0 + 9y = 40 + -34 + 7x
9y = 40 + -34 + 7x

Combine like terms: 40 + -34 = 6
9y = 6 + 7x

Divide each side by '9'.
y = 0.6666666667 + 0.7777777778x

Simplifying
y = 0.6666666667 + 0.7777777778x

See similar equations:

| 10(t-4)+4t=7(2t+3)-9 | | -56=4+6x | | x^2+4y^2=18 | | (x)(x)(x)+4x(4x+3x+2)-(x)(x)(x)+1= | | 121x^2+198x+81=0 | | 4b-7b-7+b+6B-52= | | 11t-8-19+20t+3t+10= | | (2x-1)*(x^2-4x+3)= | | 15m+2m-9-m+12-6= | | 1.4b+4.5b-2.1+3.4-1.2+3.8= | | 9a+16a= | | B=6c | | 4n-13n+-n-5= | | 8t-5t=5t+30-5t | | -10v+20+v-12= | | (-8a+a-16)(a+19)= | | 8(x-1)=2(4x-3)-2 | | w+6w+-8w+7= | | 1-x^2=x^4+2x^2+1 | | -c+8c-15+c-5c-6= | | 3(x-6)+4=5(x+2)-8 | | (-9x-x+2)+(4x+2x-7)= | | h+h+2=394 | | 22x-6-18x+3=20x-4-16x+13 | | -2(x-3)=3(-2x+4) | | 6(3+4x)-1=89 | | 0.86*7267-198= | | 2x^3+6x^2+x+3= | | 0.8(7267+300)= | | v^2=v+30 | | 0.8(x+300)=0.86x-196 | | (4x+1)(x+1)=7 |

Equations solver categories